Response of terrestrial mammals to various types of disturbance in the Gunung Merapi National Park, Indonesia - Sulaksono, Nurpana (Society for Indonesian Biodiversity, 2022)
Human disturbance in the form of sand mining and grass harvesting activities in the area of Mount Merapi is an important component of the ecological process alongside the eruption. The group of terrestrial mammals (TM) is one of the essential elements that are affected by this disturbance. Therefore, the objectives of this study were to determine the response of the TM in various types of habitats in areas affected by eruption disturbances >20 years (ERL), eruption < 20 years (ERE), mining (MIN), grazing (GRA), and non-disturbance areas (NDA) in Gunung Merapi National Park (GMNP). Camera traps were used to identify the abundance of each TM. Vegetation data were also used to represent habitat conditions and were taken on a plot of 0.04 Ha. The analysis results showed that the highest abundance of TM is at the NDA site (14.4), while the lowest is at the MIN site (2.08). The site with the highest level of TM diversity is ERL (1.97) and the lowest is NDA (1.52). Furthermore, there is a significant difference in TM abundance between the MIN and ERL sites, which indicates that each disturbance reacts differently to the site. Based on the results, mining disturbances negatively influenced the abundance of TM in GMNP, therefore, managers need to regulate mining activities and make efforts to restore the affected areas. © 2022, Society for Indonesian Biodiversity. All rights reserved.